Performance Analysis And Design Of A Arrayed Waveguide Grating (AWG) And Wavelength Conversion Device In WDM Optical Networks - Sim, Ee Chiang (2008)
In this project, a wavelength converter based on XPM and SBS is analyzed. Firstly, a sinusoidal modulated message signal is phase modulated by XPM and this phase modulated signal is then converted to amplitute modulation by SBS. The performance of the wavelength converter is then evaluated via computer simulation. The proposed novel wavelength converter is stable and immune to temperature fluctuations.